VD_FINDINFO HC / 2023 / 853 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
OBLIGATION D'ENTRETIEN, PROTECTION DE LA JEUNESSE, CHARGE FISCALE, DROIT DE GARDE | 176 al. 1 CC, 176 al. 3 CC, 285 al. 1 CC